Analisis Tingkat Kebangkrutan Dengan Menggunakan Model Altman Z-Score Pada Perusahaan Maskapai Penerbangan Yang Terdaftar Di Bursa Efek IndonesiaHety Budiyanty - Yuliana Yuliana; Hety Budiyanty; Nurman Nurman; Anwar Anwar; Andi Mustika Amin (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study aims to determine the potential bankruptcy of airline companies listed on the Indonesia Stock Exchange using the Altman Z-Score model. This research uses descriptive quantitative methods. This study aims to determine the potential bankruptcy of airline companies listed on the Indonesia Stock Exchange using the Altman Z-Score model. This research uses descriptive quantitative methods. The sample in this study is the financial statements of 3 airline companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2022 period. The data collection technique used in this study used secondary data. The data analysis technique uses the modified Altman Z-Score method. The results of this study show that PT Garuda Indonesia Tbk is in bankruptcy condition in 2016-2021, and in 2022 the company is different in gray area conditions. PT Air Asia Indonesia Tbk for seven years, namely in 2016-2022, was in bankruptcy condition. PT Indonesia Transport & Infrastructure Tbk was in bankruptcy condition in 2016-2021, and in 2022 the company was in a gray area condition..